2018
DOI: 10.2486/indhealth.2017-0174
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of low back disorders risk based on allowable weight limits for manual lifting in Iran

Abstract: In 2011, load limits for manual lifting were adopted in Iran to protect workers from low back injury without prior testing of accuracy with Iranian workers. This investigation examined how accurate the adopted ACGIH TLVs at the allowable limits predict risk for LBP disorders for a group of Iranian workers using biomechanical criteria. Testing took place in the laboratory with participants completing a series of 2-handed lifting tasks as defined in the Iranian Guideline for Manual Lifting. To test accuracy, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…The weights in the SNOOK tables, which are one of the methods for evaluating manual load lifting, should be revised (27). Afshari et al (28) in 2018, also examined the risk of occupational low back pain was also examined based on the measurable limits of lifting loads in Iran and concluded that the ACGIH TLV method requires further review based on Iranian anthropometric characteristics. Based on the results of the present study, the level of manual lifting risk obtained from WISHA and ACGIH TLV methods is different from each other and makes it difficult to decide on control methods to prevent low back disorders in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…The weights in the SNOOK tables, which are one of the methods for evaluating manual load lifting, should be revised (27). Afshari et al (28) in 2018, also examined the risk of occupational low back pain was also examined based on the measurable limits of lifting loads in Iran and concluded that the ACGIH TLV method requires further review based on Iranian anthropometric characteristics. Based on the results of the present study, the level of manual lifting risk obtained from WISHA and ACGIH TLV methods is different from each other and makes it difficult to decide on control methods to prevent low back disorders in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan analisis beban tulang belakang aktivitas MMH mengangkat galon di replika dengan menggunakan software 3DSSPP trial version yang dikembangkan oleh University of Michigan seperti pada Gambar 3. Berdasarkan Gambar 3 menunjukkan bahwa gaya kompresi pada sendi antara otot lumbal kelima dan sacral pertama (L5/S1) senilai 1644N masih cukup aman dibawah ambang batas 3400N yang disarankan National Institute of Occupational Safety and Health (NIOSH) (Afshari et al, 2018) . Hal ini dapat dipengaruhi oleh pusat gravitasi beban cukup dekat dengan posisi titik joint L5/S1 sehingga lengan momen menjadi kecil yaitu 33,4cm dengan beban 566 N dimana semakin dekat posisi beban maka kecil jarak lengan beban yang berdampak semakin kecil gaya yang dihasilkan.…”
Section: Gambar 1 Postur Aktivitas Mengangkatunclassified
“…Manual material handling (MMH) is known as one of the substantial contributors to the risk of low back pain (LBP) and other work‐related musculoskeletal disorders (MSDs) (Afshari et al, 2018; Menzel et al, 2004; Munawir et al, 2020; Rajendran et al, 2021; Zurada, 2012). Occupational jobs demanding frequent and/or heavy load lifting are strongly associated with higher rates of spinal disc degeneration and LBP (Gallagher & Marras, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent LBP, ergonomic standards are now being used in the workplace to improve the design of workstations with an emphasis on controlling various risk factors contributing to LBP such as lifting, repetitive movements, awkward postures, and forceful exertions (Afshari et al, 2018; Jakobsen et al, 2018; Matsudaira et al, 2014; Muslim & Nussbaum, 2017). A variety of risk assessment methods have been developed based on physiological, biomechanical, and psychophysical criteria, or their combinations to prevent injuries or disabilities.…”
Section: Introductionmentioning
confidence: 99%